Deregulation of DUX4 and ERG in acute lymphoblastic leukemia - Zhang, Jinghui; McCastlain, Kelly; Yoshihara, Hiroki; Xu, Beisi; Chang, Yunchao; Churchman, Michelle L; Wu, Gang; Li, Yongjin; Wei, Lei; Iacobucci, Ilaria; Liu, Yu; Qu, Chunxu; et al. (Nature genetics, 2016)
Charles Mullighan, Jinghui Zhang and colleagues characterize a subtype of B-progenitor acute lymphoblastic leukemia with deregulated DUX4 and ERG . They find that aberrant DUX4 activation results in loss of ERG function, either through deletion or by the induction a novel transforming ERG isoform, ERGalt, that inhibits wild-type ERG activity. Chromosomal rearrangements deregulating hematopoietic transcription factors are common in acute lymphoblastic leukemia (ALL). Here we show that deregulation of the homeobox transcription factor gene DUX4 and the ETS transcription factor gene ERG is a hallmark of a subtype of B-progenitor ALL that comprises up to 7% of B-ALL. DUX4 rearrangement and overexpression was present in all cases and was accompanied by transcriptional deregulation of ERG , expression of a novel ERG isoform, ERGalt, and frequent ERG deletion. ERGalt uses a non-canonical first exon whose transcription was initiated by DUX4 binding. ERGalt retains the DNA-binding and transactivation domains of ERG, but it inhibits wild-type ERG transcriptional activity and is transforming. These results illustrate a unique paradigm of transcription factor deregulation in leukemia in which DUX4 deregulation results in loss of function of ERG , either by deletion or induced expression of an isoform that is a dominant-negative inhibitor of wild-type ERG function.